Transitioning to a Greener Future: Strategies for Enhancing Employee Competencies in Indonesia Utility Company Moving Towards Renewable Energy - Febrian Robiady, Sandy; Rachmawati, Riani (Syntax Literate, 2024)
This research aims to analyze the competencies required by employees related to renewable energy at Indonesia Utility Company and to explore the challenges involved in developing IUC employees during the energy transition era. The study employs qualitative methods. this study employs both primary and secondary data. Subject Matter Experts, structural and functional ranks in charge of human resource development and the renewable energy sector were used as an samples in this study to conducting in-depth interview and Focus Group Discussion. The results of this study elucidate the presence of technical competencies, such as RE planning, ammonia and biomass co-firing, and rooftop solar PV installation. Additionally, generic competencies including Adaptability of New Technologies, Business Savvy, Critical Thinking, and Learning Agility were identified. All these competencies collectively contribute to the competency framework concerning renewable energy at Indonesia Utility Company. Other findings indicate challenges, such as the yet-to-be-validated validity and reliability of hard competence assessment methods, uneven distribution of assessments among employees, and the need for optimization in the capacity and capability development programs for employees regarding energy transition, such as the Colony program. This study provides new insights and supports the argument for the need to enhance the capacity and capabilities of employees to adapt to the energy transition towards clean energy. The existence of a competency framework that serves as guidance for IUC regarding renewable energy competencies and its support system underscores the necessity for the development of hard competency assessment tools capable of validly and reliably measuring competency levels and gaps.